High-test molasses or maize as energy source for growing pigs. Performance traits and rectal digestibility - Ly, Julio; Almaguel, R.; Lezcano, P.; Delgado, E. (Cuban Journal of Agricultural Science, 2016)
For studying productive and digestibility indices, 16 female and castrated male pigs in equal proportion from a commercial cross were distributed randomly in two groups. For six weeks, animals were fed ad libitum from 30 kg with high-test molassesor maize diets as the only energy source and torula yeast as the only protein source. Animals fed high-test molasses showed better performance (feed conversion, 4.59 and 3.45 kg DM/kg gain, P < 0.01) and rectal energy digestibility traits (83.7 and 88.1 %, P < 0.01) than those consuming maize. According to results obtained, growing pigs fed ad libitum high-test molasses diet as the only energy source can exhibit better performance traits than those receiving maize. Also, there are differences in rectal digestibility favoring the high-test molasses diet.Key words: pigs, high-test molasses, maize, performance, digestibility